MEASURING PAIN AMONG CRITICALLY ILL-INTUBATED PATIENTS: A CASE STUDY - Ardia Putra (Fakultas Keperawatan-Universitas Syiah Kuala, 2011)
ABSTRACKBACKGROUND: As a subjective concept, pain can only defined by the individual who experiencing with it, and this symptom is commonly showed by a client’s reaction to pain in intensely personal and account for the great variability from each person. Among critically ill-intubated patients, pain also being as the most common problem and more significance higher. This happen because the pain often under medicated in regard to routine procedures and treatments that must be taken for the critical patients. PURPOSE:This study aims to explore the pain management among critically-ill intubated patients in the Surgical Intensive Care Unit (SICU) and/or Surgical Respiratory Care Unit (SRCU), Songklanagarind Hospital, Hatyai, Thailand. METHOD:The study of subjects are critical care patients who administered with intubation and associated with a significant degree of pain in SICU and/or SRCU. There were 3 criterias used to collect the study subjects, included intubated patients, in medical or surgical intervention, and were able to be followed up for at least three days in ICU. There were two instruments that used in this study that consist of Demographic Data and Observational indicator, which includes vital signs, Face Rating Scale (FRS), and Critical-care Pain Observation Tool (CPOT). RESULTS: Three subjects were studied to examine their pain experiences. Some factors were founded has been influenced the level of pain among critically ill-intubated patients. These factors were included age, gender, following the surgical interventions, experiences with pain previously, fatigue, neurologic function, stress and coping mechanism, and performing nursing interventions such as endotracheal suction and mobilization/positioning. CONCLUSION:The problem of pain is more than the discomforting and it can be affected to the physical functioning and psychological problem to the patients. It is a reason that nurses should provide appropriate pain managements especially to caring the critical ill-intubated patients.Keywords: Procedural pain, pain managements, critical care nurses, and critically-ill intubated patients, pain levels, factors influence of pain.